1998
DOI: 10.1038/sj.jhh.1000608
|View full text |Cite
|
Sign up to set email alerts
|

Mild exercise activates renal dopamine system in mild hypertensives

Abstract: Objective: The role of renal dopamine in the early depressor effect of exercise was evaluated in hypertensives. Methods: After a general clinical observation period of 4 weeks, 29 essential hypertensives were divided into two groups. The exercise group (n = 16) underwent blood lactate threshold exercise using a cycle ergometer for 60 min three times a week for 4 weeks. Results: In the non-exercise group (n = 13), blood pressure (BP) and humoral variables did not change significantly (from 150 ± 3/93 ± 2 to 145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Miura et al [45], observed an increase in the levels of urinary kallikrein of hypertensive individuals submitted to 10 weeks of training in a cycloergometer. Sakai et al [46] showed that four weeks of exercise practice was able to reduce blood pressure and to increase 2-fold urinary kallikrein activity. Furthermore, we could also demonstrate that an acute exercise bout also was able to promote blood pressure reduction [9].…”
Section: Discussionmentioning
confidence: 98%
“…Miura et al [45], observed an increase in the levels of urinary kallikrein of hypertensive individuals submitted to 10 weeks of training in a cycloergometer. Sakai et al [46] showed that four weeks of exercise practice was able to reduce blood pressure and to increase 2-fold urinary kallikrein activity. Furthermore, we could also demonstrate that an acute exercise bout also was able to promote blood pressure reduction [9].…”
Section: Discussionmentioning
confidence: 98%
“…Normotensive subjects with a family history of hypertension have decreased urinary dopamine (523, 562), an impaired dopamine response to sodium loading (96,517), and a reduction in the conversion of l -DOPA to dopamine. Interestingly, mild exercise has been reported to increase renal dopamine production in Stage 1 hypertensive subjects (525). …”
Section: Structure and Function Of The Renal Dopaminergic Systemmentioning
confidence: 99%
“…BP was reduced by Ϫ8.8 (95% CL, Ϫ11.0 to Ϫ6.6)/Ϫ7.1 (95% CL, Ϫ8.6 to Ϫ5.5) mm Hg in these study groups (PϽ0.001). The 10 study groups [17][18][19]22,24,59,62,63 that reported on plasma renin activity (PRA) showed a significant decrease of PRA by 19.8% (95% CL, Ϫ35.0 to Ϫ4.7; PϽ0.05); the BP changes averaged Ϫ10.6 (95% CL, Ϫ13.9 to Ϫ7.3)/Ϫ7.0 (95% CL, Ϫ8.9 to Ϫ5.1) mm Hg (PϽ0.001).…”
Section: Changes In Plasma Norepinephrine and Plasma Renin Activitymentioning
confidence: 99%
“…Ten normotensive, 11,31,42,49,56,69 18 prehypertensive, § and 3 hypertensive study groups 23,45,79 gave no information on antihypertensive medication. Participants had been taken off medication in 2 and 6 prehypertensive 40 and hypertensive study groups, 16,19,26,29,59,64 respectively; 6 hypertensive study groups 14,30,46,54,61,71 reported that all or some of their participants were on treatment during the study. As shown in Table 1, hypertensive participants were significantly older and had a higher body mass index (BMI) than participants from other subgroups.…”
Section: Overview Of Trialsmentioning
confidence: 99%